The Relationship Between Total Output and Man-Hour Output: Comment - Klein, Lawrence R. (Quarterly Journal of Economics, 1942)
Journal Article The Relationship Between Total Output and Man-Hour Output: Comment Get access Lawrence R. Klein Lawrence R. Klein Berkeley, California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 56, Issue 2, February 1942, Pages 342–343, https://doi.org/10.2307/1881938 Published: 01 February 1942